Pengaruh Komitmen Organisasi dan Budaya Organisasi terhadap Kinerja Pegawai yang Berdampak pada Kepuasan Pelayanan Diklat di Pusat Pelatihan Manajemen dan Kepemimpinan Pertanian (PPMKP) Ciawi Bogor - Moch. Iman Imanudin (Politeknik Kelapa Sawit Citra Widya Edukasi, 2016)
The purpose of this study was to assess the influence of Organizational Commitment (X1) and Organizational Culture (X2) on Education and Training Service Satisfaction (Y) using Employee Performance (Z) as an intervening variable. The model used in this study is a model of causality or influence relationships. To examine the hypotheses proposed in this study, the analysis technique used is the path analysis. After testing and data analysis to test hypotheses proposed, this study offers the following conclusions: 1) the Organizational Commitment (X1) has smaller effect than the variable influence Organizational Culture (X2) on Education and Training Service Satisfaction (Y); 2) through Employee Performance (Z), Organizational Commitment (X1) has smaller effect compare Organizational Culture (X2) on Education and Training Service Satisfaction (Y); and 3) Employee Performance (Z) has a direct impact on the Education and Training Service Satisfaction (Y).